Involvement of Women Farmers' Groups in Agricultural Extension - Kurniasih Suryana, Nia; Zulhafandi, Zulhafandi; Rizkiani, Ella (Martabat: Jurnal Perempuan dan Anak, 2024)
Abstract: Women are often subordinated in various aspects of life, including in the realm of agriculture. Women farmer groups can play an important role in learning classes, cooperation, and production units and channelling various agricultural interests. This research aims to describe the involvement of women farmer groups in agricultural extension and formulate strategies to improve the quality of agriculture in Central Tarakan District. Data were analyzed using descriptive analysis and SWOT. The research results show that members of women farmer groups are often involved in planning extension activities, implementation and utilization of results, while involvement in supervision is still lacking. Strategies to increase the involvement of women farmer group members include: (1) providing education and training on modern agricultural techniques and the latest innovations, (2) increasing access to business credit to increase productivity and welfare, (3) providing easy access to agricultural information through information technology and communication, (4) facilitation of non-agricultural skills training such as financial management and entrepreneurship, (5) involvement of women farmer groups in planning and implementation of extension activities, and (6) development of communication networks between groups of women farmers to exchange experiences and best practices in agriculture.